2020
DOI: 10.3390/ijerph17041431
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety in Remote Monitoring of Patients with Pacemakers Five Years after an Implant: The Poniente Study

Abstract: Health-related quality of life (HRQoL) and functional capacity values immediately after pacemaker (PM) implantation have been well established; however, not much has been known about its long-term effects. The present study compared the long-term effectiveness and safety of remote monitoring plus a clinic visit versus clinic visits alone during follow-up of adults implanted with PMs. This study was a single-centre, controlled, non-randomised, non-blinded clinical trial. Data were collected pre-implantation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…SD: Standard Deviation; AF: Atrial Fibrillation; PM: Pacemakers; VAS: Visual Analogue Scale; Friedrich: Pacemaker wound infection. Source: López-Liria et al 2020 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SD: Standard Deviation; AF: Atrial Fibrillation; PM: Pacemakers; VAS: Visual Analogue Scale; Friedrich: Pacemaker wound infection. Source: López-Liria et al 2020 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of these limitations, the authors believe that the PONIENTE project is a unique study providing long-term data in an area lacking research. As the study showed no differences between the telemonitoring and conventional monitoring groups in terms of health effectiveness and safety [ 24 ], and no significant differences were found concerning patient’s experiences and communication; telemonitoring may prove to be a good option for patients with difficulties in traveling to the hospital especially nowadays that healthcare services are shifting into virtual environments wherever possible. As remote healthcare services become a central solution in the current coronavirus pandemic, patients need to adopt these new technologies [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, detailed information regarding response time and to what extent the systems are monitored is essential, as some patients have the misunderstanding that their heart rhythm is under real-time surveillance 24/7/365. Whether an increased feeling of confidence can be translated into standard measures of quality of life is, however, uncertain, as results have been conflicting in nonrandomized [ 55 ] and randomized trials [ 42 , 56 , 57 ]. However, patient satisfaction with RM is, in general, high [ 8 , 58 , 59 ].…”
Section: Convenience and Patient Satisfactionmentioning
confidence: 99%